Cattaneo-Vernotte bio-heat transfer equation. Identificaton of external heat flux and relaxation time in domain of heated skin tissue. - Mochnacki, Bohdan; Paruch, Marek (Computer Assisted Methods in Engineering and Science; Vol 25 No 2-3 (2018), 2019)
A cylindrical skin tissue domain subjected to an external heat flux is considered. Thermal processes in the domain considered are described by the Cattaneo-Vernotte equation supplemented by the appropriate boundary and initial conditions. The aim of considerations is the identification of external heat flux and relaxation time on the basis of ‘measured’ heating/cooling curves at the set of selected points located on the surface of the skin. The direct problem is solved using the implicit scheme of the Finite Difference Method (FDM), while at the stage of the inverse problem solution, the evolutionary algorithm is applied. In the final part of the paper the examples of computations are presented.